Uso de medicamentos biológicos para o tratamento da artrite reumatoide no sistema único de saúde: uma análise epidemiológica e econômica - Jéssica Barreto Ribeiro dos Santos (2019)
Introduction: expenditure on drugs dispensed by the Brazilian Unified Health System for the treatment of rheumatoid arthritis increased substantially with the start of the supply of biological drugs. Thus, the Health Technology Assessment tool has become very important in order to support decision-making regarding the incorporation and monitoring of the use of these drugs, as well as to guide health professionals and users in relation to safety, benefits and costs. Objectives: to perform a pharmacoepidemiological and pharmacoeconomic analysis of biological drugs for the treatment of rheumatoid arthritis in Brazilian Unified Health System. Methods: a historical cohort study was conducted in Brazil of individuals who started the use of the first biological drug, from January 2006 to December 2014. The proportion of persistent individuals, the mean days of persistence, and the factors associated with the discontinuation were evaluated at 12 months of follow-up. We also conducted a prospective cohort study of patients in use of the biological drugs adalimumab, etanercept and golimumab for the treatment of rheumatoid arthritis, from March 2011 to July 2017, at the Health Regional Superintendence of Belo Horizonte, Minas Gerais, Brazil. Effectiveness, functionality, quality of life, safety, expenditure and persistence of individuals were evaluated in six and 12 months of follow-up. The expenditure was stratified in two periods (March / 2011 to May / 2013 and June / 2013 to July / 2017) due to the inclusion of golimumab in 2013 and the difference in the price of these drugs between the periods. Prospective cohort analyzes were also performed for the subgroup of biological drugs naive patients. A cost-utility analysis of biological drugs adalimumab, etanercept and golimumab was performed. The parameters for the economic evaluation were obtained in the prospective cohort held in Belo Horizonte / Minas Gerais, Brazil. The perspective of the study was that of Brazilian Unified Health System and the time horizon was five years. The Markov model was used with the construction of a hypothetical cohort and cycles of six months. Health costs and benefits were discounted at present value using a discount rate of 5%. Uncertainty parameters were addressed by deterministic and probabilistic sensitivity analyzes. Results: in the historical cohort, 33,155 (49.2%) individuals persisted in treatment at 12 months. Individuals using abatacept had greater persistence in treatment, followed by golimumab, tocilizumab, etanercepte and adalimumab and, with less persistence, certolizumab and infliximab. Persistence for adalimumab, etanercept and golimumab was also evaluated by the prospective cohort, with 344 (83.9%) and 283 (69.0%) individuals persisting at six and 12 months of follow-up. There was no difference between adalimumab, etanercept and golimumab. In addition, it was verified by the prospective cohort that the patients improved after the use of the biological drugs, observing a reduction of the disease activity, improvement of the functionality and improvement of the quality of life. There were no statistically significant differences between adalimumab, etanercept and golimumab for the effectiveness, functionality and quality of life at baseline and at six and 12 months, except for functionality at six months, favoring adalimumab over golimumab. The number of patients that achieved the treatment effectiveness (remission or light activity) was 153 (37.32%) at six months and 132 (32.20%) at 12 months, respectively. The mean expenditure of patients taking adalimumab was greater than etanercept in the first follow-up period at 12 months. In the second follow-up period, mean expenditure was lower for golimumab followed by adalimumab and etanercept. The results were maintained for the subgroup of biological drugs naive patients. Golimumab was the drug with the best cost-utility ratio when compared to etanercept and adalimumab. Etanercept was dominated by golimumab, because it presented worse utility and higher cost. Adalimumab presented better utility, but higher cost. When considering a willingness to pay for a per capita gross domestic product in Brazil in 2017, golimumab remained the most cost effective alternative. The sensitivity analyzes confirmed golimumab as the most cost-effective alternative. Conclusion: in this context and in view of the high cost of biological DMARDs for BPHS and, consequently, for society, a pharmacotherapeutic follow-up should be carried out by a multidisciplinary team in order to identify the reasons for non-persistence and therapeutic failure to biological DMARDs allowing the implementation of actions for the adequate use of these drugs and, consequently, reduction of treatment costs, disease activity indexes, disease progression and disability of the RA patient, as well as improvement in quality of life. In addition, the importance of price negotiation with the manufacturer of the drug is emphasized, since the utility between adalimumab, etanercept and golimumab was similar and cost was the component that most impacted the economic model. Therefore, depending on the agreed price, adalimumab, etanercept and golimumab may alternate as the most cost-effective alternative.